The main types of training sessions in the system of lifelong learning-careers: on the example of the experience of the Institute of Advanced Training of the Ministry of Internal Affairs (MMIT Proceedings, 2024)
This article provides scientifically based information about the main types of educational and educational work in the system of continuous educational and career process of internal affairs bodies. Based on the experience of the Institute for Advanced Studies of the Ministry of Internal Affairs of the Republic of Uzbekistan.